Zakah Contribution for Community Economic Development with Analytical Networking Process Method - M Zidny Nafi' Hasbi; Ipuk Widayanti (Bulletin of Islamic Economics, 2022)
The purpose of this study is to describe theoretically and applied zakat as an Islamic financial instrument that has one function to alleviate poverty. The function of zakat is in line with the goal of sustainable community economic development which is a form of global commitment in spurring economic growth for the better. This type of research is mixed methods using the Analytical Process Networking approach. The analysis technique of this research used purposive sampling. Objects in the study include zakat management organizations, academics, government, and practitioners. The findings of this study are that the priority of implementing zakat distribution in supporting sustainable community economic development is the social aspect with a rater agreement W=0.36444. Four strategies can achieve sustainable community economic development, namely: 1) Improving the quality and quantity of concern for community social institutions and stakeholders; 2) Improve disaster risk reduction comprehensively and efficiently; 3) Improving the quality of fair law enforcement 4) Increasing job opportunities and concern for community MSMEs.